2012
DOI: 10.1186/1479-5876-10-96
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein 70 in nasopharyngeal carcinomas: different expression patterns correlate with distinct clinical prognosis

Abstract: BackgroundHeat shock protein 70, a stress protein, has been implicated in tumor progression. However, its role in nasopharyngeal carcinoma (NPC) progression has not yet been clearly investigated.MethodsImmunohistochemistry (IHC) was employed to examine the expression patterns of Hsp70, human leukocyte antigen –A (HLA-A) in NPC tissue samples.ResultsThe expression of Hsp70 exhibited different spatial patterns among nuclear, membrane and cytoplasm in 507 NPC tumor tissues. Kaplan-Meier survival analysis demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Recent data indicate that the intracellular Hsp70 is regulated in nasopharyngeal carcinoma who had metastases and its expression showed metastasis of cancer. The study by Cai et al (2012) suggest that Hsp70 intranuclear positively correlated with the classification T, N, recurrence, metastasis, clinical stage, and the type of histopathology. Intracellular extracellular Hsp70 is known as a facilitator of the immune response that can interact with receptors on the cell antigens that cause a reaction Hsp70, peptides and antigens.…”
Section: Increased Intracellular Hsp70 Expression In Nasopharyngeal Cmentioning
confidence: 92%
See 3 more Smart Citations
“…Recent data indicate that the intracellular Hsp70 is regulated in nasopharyngeal carcinoma who had metastases and its expression showed metastasis of cancer. The study by Cai et al (2012) suggest that Hsp70 intranuclear positively correlated with the classification T, N, recurrence, metastasis, clinical stage, and the type of histopathology. Intracellular extracellular Hsp70 is known as a facilitator of the immune response that can interact with receptors on the cell antigens that cause a reaction Hsp70, peptides and antigens.…”
Section: Increased Intracellular Hsp70 Expression In Nasopharyngeal Cmentioning
confidence: 92%
“…Research in China by Cai et al (2012) states that there are differences in the expression of Hsp70 intracellular with staging in patients with NPC, which is at stage III + IV expression of Hsp70 in intracellular larger 6.034 compared to stage I + II .…”
Section: Increased Intracellular Hsp70 Expression In Nasopharyngeal Cmentioning
confidence: 99%
See 2 more Smart Citations
“…We also detected cancer stem cells in NPC and proposed that genomic instability and DNA damage are among the main causes of cancer stem cell formation [2,3]. In fact, the expressions of many important genes, including p63, RASSF1A, VEGF, CCND1, and Hsp70, significantly differ in NPC tissue obtained from different patients, which we believe will affect the biological behaviors of tumors [4][5][6][7][8]. We further found that immune cells remarkably differ among NPC patients and that the expressions of various immune-related genes in tumor tissue are correlated with disease prognosis [9][10][11].…”
Section: © Higher Education Press and Springer-verlag Berlin Heidelbementioning
confidence: 99%